General Solution of Systems of Nonlinear Difference Equations with Continuous Argument - Pelyukh, G. P. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We investigate the structure of the general solution of a system of nonlinear difference equations with continuous argument in the neighborhood of an equilibrium state.